The Meaning of Symbols on Keris as a Depiction of the Identity and Character of Nusantara Society - Sutyawan, Luky; Guntur, Guntur (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to reveal the meaning of symbols on the keris that depicts the identity and character of the Nusantara society. Keris as one of Indonesia's original cultural products in the field of tosan aji has multiple functions. Keris leaves its function as a weapon and puts forward a message language for certain conditions and situations. Keris is a part of the heritage of the ancestors of the Indonesian society filled with knowledge. The knowledge in keris that stands out is the symbol system that is also present in it. This knowledge is a form of thinking of the people of the archipelago in implying their culture. The approach used in this research is the Nusantara Aesthetic approach which states that every work presented, especially in the Archipelago, always prioritises the aspects of guidance and spectacle. Keris as a cultural work of the archipelago does not only prioritise the aspect of beauty(spectacle) but also becomes a cultural work full of teachings and outlook on life(guidance) through the symbol language system presented. The symbol system in the keris then becomes a form of culture that is passed down from generation to generation as a depiction of the identity and character of the Nusantara society.